An Appraisal of Pricing Criteria by Information Producers in Iranian Scientific Research Centers - Ali HosseinPanah; Seyed Ali Akbar Famil Rohani; Mehdi Alipour Hafezi (Comparative Education Society of Iran ( CESIR), 2020)
The emergence of knowledge economy has increased diversity of intellectual services and prepared new opportunities in business for scientific research centers. The purpose of this paper is to examine the pricing criteria for information goods by Iranian scientific research centers. The research method was descriptive and statistical population included all experts of these centers in Tehran. Cluster Sampling Method was used in order to select research sample and in addition to reviewing books, journals and websites, a researcher-made questionnaire was provided. Structural equation analysis and Friedman's analysis of variance were used to analyze the data. Findings of factor analysis showed that information producers in Iran scientific and research centers mostly use the components of market structure, competition, cost, cultural and time factors as criteria for information pricing. Information producers also pay more attention to cost-oriented, competitive-oriented, marketing and sales promotion variables in pricing goals.